Driver machine-tool adaptations in the conditions of automated production - Erokhin V.V. (Научно-технический вестник Брянского государственного университета)
The article studies the actual process of formation of macro deviations of the machined surface of the billet taking into account the design and technological parameters of machine tools. It is shown that the work surfaces of the workpiece parallel to the support surfaces that form the installation or double guiding base have the lowest values of the shape and location errors. The error in the theoretical results given in the article, relative to the experimental values of the shape errors, is 12 … 20%. The technique for designing an automated system for investigating the effect of structural parameters of machine tools on the accuracy of workpiece machining for the purpose of accumulating and processing information for design and technological purposes is presented.